PERBANDINGAN KEBOCORAN MIKRO PADA RESTORASI RESIN KOMPOSIT MIKROFILLER DENGAN RESIN-MODIFIED GLASS IONOMER CEMENT (RMGIC) PADA KAVITAS KLAS V GIGI ANTERIOR - Thesi Kurnia Ayudia; Kuswardani Susari Putri; Ivony Fitria (Andalas Dental Journal, 2015)
Microleakage defined as the clinically undetectable passage of bacteria, fluids, molecules or ions between a cavity wall and the restorative material. Microleakage tends to occur in Class V cavities. It is caused by marginal adaptation which is more difficult in class V cavities. Microfiller composite resin is developed and indicated for areas that not require a large pressure. As the development of dental materials, it has been developed a composite resin base material that is known as resin-modified glass ionomer cement. This material has purposed to reduce the limitation of conventional glass ionomer cement and take the advantage of the composite resin material. The aim of this study was to evaluate microleakage difference of microfiler composite resin restoration with resin-modified glass ionomer cement restorations in class V anterior teeth cavities. The methode of this study used experimental laboratory through in vitro process . Thirty two class V cavities were prepared on labial surfaces of extracted human anterior teeth. Samples were divided into two groups. Group I included sixteen samples that have had restorated with microfiller composite. Group II included sixteen samples that have had restorated with resin-modified glass ionomer cement. The samples were immersed into aquabides solution for 24 hours. After that, the samples were immersed into 1% methylene blue solution for 24 hours. All samples sectioned longitudinally and analyzed for microleakage as dye penetration using a stereomicroscope. Student t-test were used for statistical analysis. The resulting data showed no significantly difference between two groups. Key Word : Microleakage, microfiller composite resin, resin-modified glass ionomer cement (RMGIC), class V cavities.